BRIGHTNESS-MODE EKOCARDIOGRAPHY ON THE PHYTON SNAKES - Ulum, Mokhamad Fakhrul; Lestari, Nurul Aeni Ayu; Pertiwi, Amira Putri; Kombo, Muhammad Piter; Tumbelaka, Ligaya Ita (Buletin Veteriner Udayana, 2019)
Echocardiography is one of the health diagnostic techniques of cardiac organ by utilizing high-frequency sound waves that are non-invasive, safe, fast, and easy to do. This echocardiography study aims to observe the structure, position, and size of cardiac organ in the three species of phyton (Sanca), namely Sanca batik, Sanca bodo, and Sanca bola. The cardiac organs were imaged using ultrasonography of brightness mode with a 10 MHz linear type transducer and using a water medium as an ultrasound gel. Snakes were handled and restrained physically, without the use of sedation or anesthesia. The position of the cardiac organ is measured by the number of the ventral scales, while the size of the cardiac organ is measured by the sum of the number of ventral scales. The results indicate that the position of the cardiac organ is at the number 55-77 ventral scales, while the size of the cardiac organ ranges from 12-13 ventral scales. The position of the cardiac organ on Sanca batik tends to be more anterior than Sanca bodo and Sanca bola. Ultrasonographic in longitudinal standard view shows the cardiac parts of the sinus venosus, right atrium, left atrium, cavum arteriosum, cavum venosum, cavum pulmonale, pulmonary artery, and aorta. Whereas in transversal standard view shows parts of cavum venosum, cavum pulmonale, cavum arteriosum, and aorta. The muscle of the cardiac organs has a gray (hypoechoic) echogenicity with a blood vessel that appears to be black (anechoic). While the more clayey’s cardiac tissue appeared as white color (hyperechoic).